2011
DOI: 10.5007/1980-0037.2009v11n3p299
|View full text |Cite
|
Sign up to set email alerts
|

Nível de atividade física e comportamento sedentário em escolares

Abstract: Resumo -Este trabalho objetivou verificar o nível de atividade física (NAF) e o comportamento sedentário em escolares da cidade de Aracaju (SE). Participaram do estudo 1028 estudantes de ambos os sexos, com uma média de 15,38 (2,44) e 15,24 (2,40) anos de idade para o sexo feminino e masculino, respectivamente. Da amostra, 24,7% eram crianças e 75,3% adolescentes, com uma média de 12,07 (0,88) e 16,39 (1,72) anos de idade, respectivamente. Utilizou-se um instrumento já aplicado em estudos nacionais, com o qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
17

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 17 publications
4
17
0
17
Order By: Relevance
“…In Brazil, there are no standardised instruments, direct or indirect, to estimate physical inactivity among young people 22 . All studies have used indirect methods to assess physical activity (i.e., methods that use reports from the individuals themselves).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there are no standardised instruments, direct or indirect, to estimate physical inactivity among young people 22 . All studies have used indirect methods to assess physical activity (i.e., methods that use reports from the individuals themselves).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity at school and at play was considered in this case 18 . A study of school-aged children and adolescents from Aracaju, also using the PAQ-C, showed similar data with a prevalence of inactivity of 85.2% for girls and 69.8% for boys 23 . Another study of schoolchildren in the city of Curitiba-PR between the ages of 14 to 18 showed that 77.9% of the boys and 90.9% of the girls are insufficiently active, and the outcome was defined as not achieving five days of moderate or vigorous physical activity per week 24 .…”
Section: Resultsmentioning
confidence: 53%
“…Uma das metas do Plano de Ações Estratégicas para o enfrentamento das DCNT no Brasil 2011-2022 (BRASIL, 2011) é aumentar os níveis de atividade física no lazer da população brasileira, pelo fato de que esse grupo de doenças constitui "o problema de saúde de maior magnitude e correspondem a cerca de 70% das causas de mortes". Na análise por sexo, estudos identificaram que baixos níveis de atividade física estão presentes com maior prevalência no sexo feminino (OLIVEIRA et al, 2012;FARIAS JÚNIOR et al, 2009;SILVEIRA;SILVA, 2011;SILVA et al, 2009;PELEGRINI;PETROSKI, 2009;GONÇALVES et al, 2007;OEHLSCHLAEGER et al, 2004). O presente estudo não teve objetivo de identificar a prevalência de adolescentes que atingiram ou não os níveis recomendados de atividade física.…”
Section: Discussionunclassified
“…Fis/UEM, v. 23, n. 4, p. 635-645, 4. trim. 2012 feminino, mais velhos, filhos de pais com baixa escolaridade provenientes de família com baixo poder aquisitivo, e com estilo de vida inadequado são os grupos mais vulneráveis aos baixos níveis de atividade física (OLIVEIRA et al, 2012;PELEGRINI;PETROSKI, 2009;SILVA et al, 2009;FARIAS JÚNIOR et al, 2009;HALLAL et al 2003). Tais informações são importantes, pois podem subsidiar políticas de promoção da atividade física entre os adolescentes.…”
Section: Introductionunclassified
See 1 more Smart Citation